2023
DOI: 10.3390/v15020415
|View full text |Cite
|
Sign up to set email alerts
|

Virally Suppressed People Living with HIV Who Use Opioids Have Diminished Latency Reversal

Abstract: Of the 12 million people who inject drugs worldwide, 13% live with HIV. Whether opioid use impacts HIV pathogenesis and latency is an outstanding question. To gain insight into whether opioid use influences the proviral landscape and latent HIV reservoir, we performed intact proviral DNA assays (IPDA) on peripheral blood mononuclear cells (PBMCs) from antiretroviral therapy (ART)-suppressed people living with HIV (PWH) with or without current opioid use. No differences were observed between PWH with and withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
1
3
1
Order By: Relevance
“…Overall, participants were matched on the duration of ART and the duration of virus suppression, key variables that have been associated with HIV-1 reservoir size, 54 and our urine toxicology results were consistent with the participants' ascribed opioid use group. We found that opioid use generally did not impact LRA responsiveness, in contrast to a recent smaller study 41 . Our relatively large sample size allowed us to determine that this potency was less likely to be affected by sex, race, or ethnicity.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Overall, participants were matched on the duration of ART and the duration of virus suppression, key variables that have been associated with HIV-1 reservoir size, 54 and our urine toxicology results were consistent with the participants' ascribed opioid use group. We found that opioid use generally did not impact LRA responsiveness, in contrast to a recent smaller study 41 . Our relatively large sample size allowed us to determine that this potency was less likely to be affected by sex, race, or ethnicity.…”
Section: Discussioncontrasting
confidence: 99%
“…Here we found no effects of opioid use by indication, type, or pharmacology on markers of HIV-1 persistence. In the setting of persistently suppressed viremia, opioid use was less likely to modulate virus reservoir size, findings that agree with recent studies of injection heroin use (47, 63). Overall, participants were matched on the duration of ART and virus suppression, key variables that have been associated with HIV-1 reservoir size (64), and our urine toxicology results were consistent with the participants’ ascribed opioid use group.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…On the contrary, a recent ex vivo study using PBMCs from PWH on suppressive ART reported no differences in HIV intact and defective reservoir and reduced HIV-1 reactivation after stimulation through anti-CD3/CD28 beads in participants on opioids compared to those not on the drugs; this was correlated to repressed inflammatory cytokine responses (namely TNFα) [ 52 ]. However, the study had a limited sample size and high heterogeneity in the type and dose of opioids, as well as in the HIV-related characteristics of participants which may explain the discrepancy of these findings compared to other findings reported herein.…”
Section: Opioids and Hiv Latencymentioning
confidence: 99%